(untitled) (The Spectrum, 2026)
This introduction offers an overview of academic writing and publishing in the contemporary moment marked by the rapid uptake of generative artificial intelligence (GAI) basically drawing on experiences from managing submissions to a locally based interdisciplinary journal. It briefly discusses authorship, ethics, and human knowledge production. It engages critical perspectives on technology and tries to think through the implications this perspective may have for current situation. GAI intensifies textual excess, complicates authorship, and reinforces neoliberal publish‑or‑perish imperatives that may risk the importance of pause and reflection needed to accomplish scholarly work. We have tried to reorient the attention toward an ethical and intellectual practice grounded in judgment, responsibility, and pause. We suggest Aristotle’s ideas on virtue ethics could be worth considering cultivating writerly virtues and character as essential to academic flourishing. We conclude that reflective, relational, and locally grounded publishing practices that place human judgment and ethical deliberation could be one way to think about scholarly communication in the age of AI.